The Effect of space planting on Growth of Mangrove (Avicennia marina) Seedlings in The Anak Setatah Village, West Rangsang District Meranti Archipelago Riau Province - Ari yanto rama doni; Syafruddin Nasution; Feliatra ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in Febuary - April 2016 at Anak Setatah Village, West Rangsang District Meranti Archipelagos Riau Province. This study aims to determine the effect of spacing on seedling height, survival rateand leave number of A. marina. The method used was experiment method. Planting space treatment were 25, 50 and 75 cm. The result for 60 days of observation show that the best space in high found in plant spacing 75 cm with a value of 26,04 cm/60 days, and the best growth for diameter was at space of 25 cm, with a stem diameter growth of 0.41 cm/60 days. The highest number of leaves in a spacing of 75 cm. The Anova test results that spasing planting given effect to height grow, stem diameter, and total number of leafs A. marina. Student- Newman- Keuls test show that treatment 25 cm is diffirent with 50 cm, and 75 cm, but treatment 50 cm is not diffirent with 75cm.Keywords: Avicennia marina, growth, and planting space.